THE PERSISTENCE OF COLONIALITY IN INDONESIAN EDUCATION: A TAN MALAKA-FREIREAN READING - Elin Wijaya (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This article analyzes the Merdeka Curriculum and the idea of Merdeka Belajar (Independent Learning) as a contestation of the meaning of “independence” in education. The study distinguishes procedural independence in terms of flexibility of methods, differentiation, and simplification of content from substantive independence in critical pedagogy, namely liberation from oppressive power relations. The research uses literature study and conceptual-critical analysis of policy documents and the literature of Tan Malaka and Paulo Freire. The findings show that the novelty of the Merdeka Curriculum appears strong at the methodological level, but it is still vulnerable to maintaining the coloniality of education at the structural level. This vulnerability is seen in three axes: knowledge power that remains rooted in official knowledge, evaluation that maintains the function of selection and reproduces achievement hierarchies, and goal orientation that easily shifts to become instrumental and compatible with human capital logic. Paradoxically, students appear autonomous in their learning methods but remain locked into comparative measures of success. These findings confirm that curriculum reform needs to touch on epistemic structures and assessments in order for education to move towards emancipation. The Tan Malaka-Freire synthesis framework is offered to evaluate policies and formulate the conditions for substantive independence in learning practices in schools and campuses